Epstein-Barr virus-positive mucocutaneous ulcer: A unique case occurring in association with cholelithiasis in a gallbladder - Flavin, Richard; Ravi, Narayanasamy (My University, 2020)
Epstein-Barr virus (EBV)-positive mucocutaneous ulcer is a lymphoproliferative disorder occurring in patients due to iatrogenic or age-related immunosuppression confined to the oropharynx, skin, and gastrointestinal tract. Here, we report the first case to our knowledge of EBV-positive mucocutaneous ulcer occurring in a gallbladder.
PUBLISHED
Keywords: Cholelithiasis; EBVMCU; Epstein‐Barr Virus; Gallbladder; Cancer